JURNAL NASIONAL TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI: Peningkatan Kapasitas Penyisipan Audio Data Hiding Berbasiskan Modifikasi Metode Least Significant Digit - Tegar Palyus Fiqar, Tohari Ahmad (Teknik elektro UGM, 2017)
Nowadays, the needs of data security is proportional to the amount of data usage as the effect from easiness in internet access. There are many ways to protect data in order to avoid data leakage, such as cryptography, watermarking, and data hiding. The latter is conducted by hiding secret data into a carrier. A popular method in data hiding is Least significant digit (LSD). The hiding is carried out by changing the value of binary secret data into decimal in specific segment. Then, the decimal value of secret data is inserted into the carrier. The process in LSD method is relatively simple and easier to implement, but the LSD has weakness in pivoting point as reference of data changes. This results in a change into the original data carrier. Additionally, this also has limited amount of data capacity that can be inserted.